Titanium imido complexes of cyclooctatetraenyl ligands. - Dunn, S; Hazari, N; Jones, N; Moody, A; Blake, A; Cowley, A; Green, J; Mountford, P (2005)
Reaction of [Ti(NR)Cl2(py)3] (R=tBu or 2,6-iPr2C6H3) with K(2)[COT] (COT=C8H8) or Li2[COT''] (COT''=1,4-C8H6(SiMe3)2) gave the monomeric complexes [Ti(NR)(eta8-COT)] or [Ti(NR)(eta8-COT'')], respectively. The pseudo-two coordinate, "pogo stick" geometry for these complexes is unique in both early transition-metal and cyclooctatetraenyl ligand chemistry. In contrast, reaction of [Ti(N-2,6-Me2C6H3)Cl2(py)3] with K2[COT] gave the mu-imido-bridged dimer [Ti2(mu-N-2,6-Me2C6H3)2(eta8-COT)2]. It appears that as the steric bulk of the imido and C8 ring substituents are decreased, dimerisation becomes more favourable. Aryl imido COT complexes were also prepared by imido ligand exchange reactions between anilines and [Ti(NtBu)(eta(8)-COT)] or [Ti(NtBu)(eta(8)-COT'')]. The complexes [Ti(NtBu)(eta(8)-COT)], [Ti(N-2,6-iPr2C6H3)2(eta8-COT)] and [Ti2(mu-N-2,6-Me2C6H3)2(eta8-COT)2] have been crystallographically characterised. The electronic structures of both the monomeric and dimeric complexes have been investigated by using density functional theory (DFT) calculations and gas-phase photoelectron spectroscopy. The most striking aspect of the bonding is that binding to the imido nitrogen atom is primarily through sigma and pi interactions, whereas that to the COT or COT'' ring is almost exclusively through delta symmetry orbitals. A DFT-based comparison between the bonding in [Ti(NtBu)(eta8-COT)] and the bonding in the previously reported late transition-metal "pogo stick"complexes [Os(NtBu)(eta6-C6Me6)], [Ir(NtBu)(eta5-C5Me5)] and [Ni(NO)(eta5-C5H5)] has also been undertaken.